2016
DOI: 10.5714/cl.2016.19.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrochemical oxidation of carbon fibers on interfacial shear strength using a micro-bond method

Abstract: In this work, we studied the effects of electrochemical oxidation treatments of carbon fibers (CFs) on interfacial adhesion between CF and epoxy resin with various current densities. The surface morphologies and properties of the CFs before and after electrochemical-oxidation-treatment were characterized using field emission scanning electron microscopy, atomic force microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and single-fiber contact angle. The mechanical interfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This improved the interfacial shear stength with an epoxy matrix by nearly 10% and increased the fiber tensile strength by 16%. In a similar study, carbon fibers electrochemically oxidized in aqueous ammonium bicarbonate solution showed a 40% improvement of interfacial shear strength in an epoxy matrix, while preserving carbon fiber mechanical strength . Figure compares the fracture morphologies of micro‐bond test specimens containing untreated and electrochemically oxidized carbon fibers.…”
Section: Interfacial Engineeringmentioning
confidence: 80%
“…This improved the interfacial shear stength with an epoxy matrix by nearly 10% and increased the fiber tensile strength by 16%. In a similar study, carbon fibers electrochemically oxidized in aqueous ammonium bicarbonate solution showed a 40% improvement of interfacial shear strength in an epoxy matrix, while preserving carbon fiber mechanical strength . Figure compares the fracture morphologies of micro‐bond test specimens containing untreated and electrochemically oxidized carbon fibers.…”
Section: Interfacial Engineeringmentioning
confidence: 80%
“…To further illustrate the chemical state of surface-treated CFs, some researchers have also quantified the hydrophilicity through measuring the contact angles of CFs [ 29 ]. Meanwhile, a single CF pullout test has been conducted to evaluate the mechanic performance of CFs with different surface microstructures [ 1 , 30 , 31 ]. These investigations have led to many significantly deepened understandings of the CF surface microstructure and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although all the above investigations have clearly indicated that strong polarization can alter the surface state of a CF, no effort has been made to look into the detailed electrochemical activity and surface morphology changes in particular, because most of the studies were simply aimed at improving the adhesion of CFs to their matrix materials [ 21 , 25 , 30 , 39 ]. However, in practice, CF may be strongly polarized if it is used as an electrochemical sensor or reinforcement for carbon fiber reinforced polymers (CFRPs) in a service environment with stray current densities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, CF has drawn more attention in composite design where anisotropic high thermal conductivity, large mechanical load transfer, and light weight are desirable. However, the inertness of the CF surface and the difference in its surface energetics with polymers play a key role in the integrity and properties of the final multicomponent system [12][13][14][15]. Therefore, the challenge addressed here is to enhance the interfacial adhesion between the matrix and the filler using the proper interfaces to obstruct the boundary phonon scattering while buffering the electrical conductivity of CFs for a better and safer performance in electronic units.…”
Section: Introductionmentioning
confidence: 99%